2022
DOI: 10.1186/s12915-022-01250-1
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented organelle genomic variations in morning glories reveal independent evolutionary scenarios of parasitic plants and the diversification of plant mitochondrial complexes

Abstract: Background The morning glories (Convolvulaceae) are distributed worldwide and produce economically important crops, medicinal herbs, and ornamentals. Members of this family are diverse in morphological characteristics and trophic modes, including the leafless parasitic Cuscuta (dodders). Organelle genomes were generally used for studying plant phylogeny and genomic variations. Notably, plastomes in parasitic plants always show non-canonical features, such as reduced size and accelerated rates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 119 publications
5
19
0
Order By: Relevance
“…S1, Supplementary Material online). We also find that all Cuscuta we sampled possess fragmented ccmFc genes, in which exon 1 splits into two pieces, consistent with the observation in recent studies ( Anderson et al 2021 ; Lin et al 2022 ). Based on the phylogeny, each parasitic lineage is also grouped together with their autotrophic relatives with high support ( fig.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…S1, Supplementary Material online). We also find that all Cuscuta we sampled possess fragmented ccmFc genes, in which exon 1 splits into two pieces, consistent with the observation in recent studies ( Anderson et al 2021 ; Lin et al 2022 ). Based on the phylogeny, each parasitic lineage is also grouped together with their autotrophic relatives with high support ( fig.…”
Section: Discussionsupporting
confidence: 92%
“… Anderson et al (2021) concluded that the apparent lack of mitochondrial HGT in Cuscuta may be due to the relatively small size of their mitogenomes, which limits the capacity to integrate foreign DNA. Supporting this notion is a recent finding of “HGT-like” sequences that have been reported within the mitogenome of C. japonica ( Lin et al 2022 ). In this species, belonging to subg.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations